2011
DOI: 10.1016/j.ijgo.2010.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Length of the endometrial cavity and intrauterine contraceptive device expulsion

Abstract: The present results do not support the hypothesis of an association between uterine length and risk of intrauterine contraceptive expulsion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 23 publications
(34 reference statements)
0
17
0
Order By: Relevance
“…12,17,18 Our study found that women with a greater LTD had a higher risk of expulsion or displacement among MLCu375 or TCu380A users. To the best of our knowledge, few studies have investigated the association between expulsion and LTD, as measured by ultrasound.…”
Section: Discussionmentioning
confidence: 64%
“…12,17,18 Our study found that women with a greater LTD had a higher risk of expulsion or displacement among MLCu375 or TCu380A users. To the best of our knowledge, few studies have investigated the association between expulsion and LTD, as measured by ultrasound.…”
Section: Discussionmentioning
confidence: 64%
“…Risk factors include young age, nulliparity and immediately postpartum. The rate of expulsion is not related to the uterine cavity length (Bahamondes, et al, 2011) …”
Section: Complicationsmentioning
confidence: 88%
“…The expulsion rate was higher for women with an endometrial cavity length equal to or greater than 45 mm (p<0.01) for one or two years. On the other hand, Bahamondes MV et al [20] evaluated the correlation between endometrial cavity length and expulsion rate in acceptors of the TCu380A intrauterine device (IUD) or the levonorgestrel-releasing intrauterine system (LNG-IUS). Their results do not support the hypothesis of an association between uterine length and risk of intrauterine contraceptive expulsion [20].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Bahamondes MV et al [20] evaluated the correlation between endometrial cavity length and expulsion rate in acceptors of the TCu380A intrauterine device (IUD) or the levonorgestrel-releasing intrauterine system (LNG-IUS). Their results do not support the hypothesis of an association between uterine length and risk of intrauterine contraceptive expulsion [20]. In a study, when cases were compared to nonpregnant controls with IUD, the results showed that uterine position and hysterometric measurements were not associated with an increased risk of pregnancy.…”
Section: Discussionmentioning
confidence: 99%